Exploring EFL Students Communication Strategies Online and Offline EFL Learning - Fadliyah, Andi Ayu; Syarifuddin, Syarifuddin; Sahril, Sahril; Aba, Akbar (Journal of Education Technology Information Social Sciences and Health, 2024)
This study aims to identify students’ ability to use communication strategies in online and offline learning through the interaction between students and teacher at SMA Muhammadiyah 1 Unismuh Makassar. The researcher applied a descriptive qualitative research method to identify the results of students’ ability in communication strategy. The population of this research is students of SMA Muhammadiyah 1 Unismuh Makassar. The data collected by distributing questionnaire and taking of video record, and transcribing them during the learning process specifically for qualitative data. From this result of the data, in online communication strategies that students use more Appeal for Help, with the highest of 85.55%. In offline learning communication strategy of students uses the Code-Switching strategy. For online learning students’ communication strategies teacher is more likely to provide direction and assistance to students’ causes students are less able to understand. In offline learning students more likely to use languages in interacting, which uses Indonesian and English in the same time.